2021
DOI: 10.1111/psyg.12770
|View full text |Cite
|
Sign up to set email alerts
|

Associations of depressive symptoms and perceived social support with addictive use of social media among elderly people in Turkey

Abstract: Background The aim of this study was to investigate the relationship of addictive use of social media (AUSM) with depressive symptoms, perceived social support and demographic variables among people aged 65 years and older. Methods People aged 65 years and older who use social media constituted the study sample. The data were obtained from social networking sites via Google survey link. Bergen social media addiction scale (BSMAS) for determining AUSM, Multidimensional Scale of Social Support for determining so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…So, more attention should be paid to the older adults’ Internet addiction, as the old are prone to use the internet excessively because of their lack of social support and physical activity and experience high loneliness when they are addicted to the internet ( Meshi et al, 2020 ). Although existing research findings have showed that social support and loneliness are strong predictors of Internet addiction ( Bozoglan et al, 2013 ; Wu et al, 2016 ; Özbek and Karaş, 2022 ), it is an intriguing question whether the emotional support of family (e.g., interaction with children) has a unique effect on Internet addiction among the old, or whether this association will be mediate by loneliness. Besides, results from the role of life satisfaction in the prevention of loneliness has revealed that life satisfaction is devoted to reducing feelings of loneliness ( Andrew and Meeks, 2018 ) and life satisfaction can help explain why some are more prone to Internet addiction while others are less ( Lachmann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So, more attention should be paid to the older adults’ Internet addiction, as the old are prone to use the internet excessively because of their lack of social support and physical activity and experience high loneliness when they are addicted to the internet ( Meshi et al, 2020 ). Although existing research findings have showed that social support and loneliness are strong predictors of Internet addiction ( Bozoglan et al, 2013 ; Wu et al, 2016 ; Özbek and Karaş, 2022 ), it is an intriguing question whether the emotional support of family (e.g., interaction with children) has a unique effect on Internet addiction among the old, or whether this association will be mediate by loneliness. Besides, results from the role of life satisfaction in the prevention of loneliness has revealed that life satisfaction is devoted to reducing feelings of loneliness ( Andrew and Meeks, 2018 ) and life satisfaction can help explain why some are more prone to Internet addiction while others are less ( Lachmann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate potential confounding effects, referring to the study by Meshi et al (2020) and Özbek and Karaş (2022) , we took demographic information of the employees, including age, gender, education level, living with children, and estimated daily time on internet, as control variables. Meanwhile, we also controlled for number of children and taking care of grandchildren.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations